Charter and Revised Ordinances of the City of Los Angeles 39 (1873) - (:unkn) unknown (My University, 1873)
§ 23: Prohibited discharge of any gun, pistol, rifle, or other description of fire-arms, or discharge of any air-gun within city fire limits. Violators fined give dollars for the first offence, ten dollars for the second offense, and not more than fifty dollars and imprisonment not exceeding ten days on the third offense.
Keywords: DISCHARGE